2021
DOI: 10.1021/acsaelm.1c00417
|View full text |Cite
|
Sign up to set email alerts
|

Ion Beam-Mediated Defect Engineering in TiOx Thin Films for Controlled Resistive Switching Property and Application

Abstract: Defect density and its migration under the influence of an applied electric field plays a crucial role for memristors toward designing a fundamental element of neuromorphic computing, e.g., an artificial synapse. Therefore, to have tunable performance, even at the nanoscale, it is essential to have better control over the defect density, albeit achieving it with direct growth methods remains a challenge. Here, we demonstrate an effective and robust approach to tune the defect density and consequently resistive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 63 publications
0
10
0
Order By: Relevance
“…Hwang et al reported significant improvement of conduction modulation linearity and pattern recognition efficiency upon increasing V O s concentration in Ta 2 O 5 thin films [20]. In case of TiO x -based memristors increase of V O s by means of ion beam irradiation, as well as incorporation of a V O -rich TiO y layer have been found to improve their neuromorphic characteristics [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…Hwang et al reported significant improvement of conduction modulation linearity and pattern recognition efficiency upon increasing V O s concentration in Ta 2 O 5 thin films [20]. In case of TiO x -based memristors increase of V O s by means of ion beam irradiation, as well as incorporation of a V O -rich TiO y layer have been found to improve their neuromorphic characteristics [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…[30] In general, various intrinsic and extrinsic methods can be employed to gain control over the defect-dependent switching properties. [3,[30][31][32][33][34][35] In the former case, the concentration of cationic/anionic vacancies is modified during the film growth process, [34] whereas, in the latter case, impurity doping of the switching medium is considered either during growth or post-growth processing. [30] For instance, Ag-cluster-doped TiO 2based two-terminal memristor exhibits an improved artificial synaptic performance.…”
Section: Introductionmentioning
confidence: 99%
“…[26] In addition, recently Choi et al have reported better switching performances in Si-Ge-based epitaxial memristors via defect engineering by means of structural modifications. [3] On another note, ion implantation is also considered to be an extremely useful technique not only to modulate post-growth defect density within the switching medium [30] but also to give rise to self-organized pattern formation on its surface, depending on the ion-energy, -fluence, and incident angle. [30,32] As a result, anisotropic, electrical, [36] magnetic, [37,38] and optical properties [39,40] are realized.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations